Katianna maryae n. sp. (Collembola: Katiannidae), a southern Appalachian species of a Gondwanan genus - Bernard, Ernest C. (Zootaxa, 2014)
Katianna maryae n. sp. is described from turf and grassy fields in eastern Tennessee, USA. This species is the first of its genus to be noted from temperate North America. It is distinguished from other described Katianna spp. by a combination of the following characters: color pattern of body an intricate mosaic of purple-brown, yellow-orange and white; copper-brown median stripe between eye patches; fourth antennal segment annuliform but not subsegmented; region between interantennal and clypeal region devoid of setae, clypeal region with six rows of setae; fore and middle feet with 8 clavate tenent hairs, hind foot with 6; apical filament of unguiculus long on fore and middle tibiotarsi, short on hind tibiotarsus; unguis with intricate multidentate pseudonychia; posterior face of dens with one proximal seta and a pair of subapical setae.